Volume growth in the component of the Dehn-Seidel twist - Frauenfelder, Urs; Schlenk, Félix (My University, 2005)
We consider an entropy-type invariant which measures the polynomial volume growth of submanifolds under the iterates of a map, and we show that this invariant is at least 1 for every diffeomorphism in the symplectic isotopy class of the Dehn-Seidel twist.
Keywords: LAGRANGIAN INTERSECTIONS; SYMPLECTIC ACTION; FLOER COHOMOLOGY; MORSE-THEORY; HOMOLOGY; PERIODICITY; GEOMETRY; ENTROPY